2010
DOI: 10.1038/mp.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric disease risk factors DISC1 and TNIK interact to regulate synapse composition and function

Abstract: Disrupted in schizophrenia 1 (DISC1), a genetic risk factor for multiple serious psychiatric diseases including schizophrenia, bipolar disorder and autism, is a key regulator of multiple neuronal functions linked to both normal development and disease processes. As these diseases are thought to share a common deficit in synaptic function and architecture, we have analyzed the role of DISC1 using an approach that focuses on understanding the protein– protein interactions of DISC1 specifically at synapses. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 57 publications
4
141
2
Order By: Relevance
“…In contrast, biological studies of DISC1 have been rigorously taken place based on solid discovery of the DISC1 gene in the original Scottish pedigree, indicating that the DISC1 pathway can underlie the endophenotypes relevant to a wide range of psychiatric disorders, in particular, schizophrenia and depression (2). DISC1 interacts with many proteins, and its regulatory roles in synaptic plasticity may be multiple (10,12,19,20). It remains elusive how these multiple mechanisms interact with each other for the overall synaptic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, biological studies of DISC1 have been rigorously taken place based on solid discovery of the DISC1 gene in the original Scottish pedigree, indicating that the DISC1 pathway can underlie the endophenotypes relevant to a wide range of psychiatric disorders, in particular, schizophrenia and depression (2). DISC1 interacts with many proteins, and its regulatory roles in synaptic plasticity may be multiple (10,12,19,20). It remains elusive how these multiple mechanisms interact with each other for the overall synaptic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, more than one mechanism has been proposed in regard to the regulation of synaptic plasticity and maintenance by DISC1 (10,19,20). For example, DISC1 negatively regulates access of Kalirin-7 (Kal-7) to a small GTPase protein Rac1 and contributes to proper control of Rac1 activation and synaptic maintenance: this mechanism participates in the spine change triggered by NMDA-R activation (10).…”
mentioning
confidence: 99%
“…DISC1 is a scaffolding protein that is thought to coordinate other synaptic proteins (30)(31)(32), and indeed plays a key role in synaptic spine maintenance in association with the activation of NMDA receptors (33). Thus, we hypothesized that the results from the unbiased approach might reflect a possible defect of a molecular pathway involving DISC1 in the synapse.…”
Section: Nmda Receptor Deficient Mice Show An Age-dependent Deficit Inmentioning
confidence: 99%
“…It has been found that DISC1 interacts with multiple proteins, such as the second messenger PDE4B, which hydrolyzes cAMP and regulates the PKA signaling pathway (4), the transcription factor ATF4/CREB2, which controls gene expression (38), and the motor protein kinesin 1, which mediates the microtubule-based transport of neuronal cargos (32). The role of DISC1 in regulating glutamate receptors and spine synapses has been documented (17)(18)(19). In this study, we revealed the role of DISC1 in regulating GABA A receptors and synaptic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…DISC1 is enriched in the postsynaptic density of excitatory synapses (16), where it regulates spine size, spine number, and AMPA receptor synaptic trafficking via a kalirin 7-Rac1-PAK pathway (17). DISC1 also regulates synapse maintenance through interacting with TRAF2 and NCK-interacting protein kinase (TNIK) (18) and exerts an important effect on NMDA receptor expression and function through a mechanism depending on the transcription factor cAMP response elementbinding protein (19). DISC1 has also been found at inhibitory synapses (16).…”
mentioning
confidence: 99%